1961
DOI: 10.1128/jb.82.4.511-516.1961
|View full text |Cite
|
Sign up to set email alerts
|

Specific Effect of Limiting Nutrient on Physiological Events During Culture Growth

Abstract: In cultures of Escherichia coli strain K12, the sequence of physiological events at the time of growth cessation in populations limited by availability of carbon source (glucose), nitrogen source (ammonium sulfate), and oxygen was observed to differ in several respects. These included differences in the relationship between mass synthesis and cell division, the utilization of nonlimiting nutrients, and the nature of changes in energy metabolism. These observations are discussed with reference to problems invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

1969
1969
1974
1974

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 9 publications
1
25
1
Order By: Relevance
“…Citrate was determined by the method of Marier and Boulet (23). Glucose was determined by the modified anthrone method of Ecker and Lockhart (8). The protein in cell-free extracts was determined by the method of Lowry et al (20) with bovine serum albumin used as the standard.…”
mentioning
confidence: 99%
“…Citrate was determined by the method of Marier and Boulet (23). Glucose was determined by the modified anthrone method of Ecker and Lockhart (8). The protein in cell-free extracts was determined by the method of Lowry et al (20) with bovine serum albumin used as the standard.…”
mentioning
confidence: 99%
“…If the cells were not used iimnediately they were frozen at -20 C until needed. It has been demonstrated that such storage procedures do not affect the analytical determinations (Ecker and Lockhart, 1961b). When the cells were to be used they were resuspended in 5 ml Sorenson's phosphate buffer, pH7, and centrifuged for 20 min at 1800 X g. Sang)les of the culture supernatant were held at -20 C until analyzed.…”
Section: Culture Systemsmentioning
confidence: 99%
“…The residual substrate in the culture effluent was determined in order to confirm the growth limiting conditions. Ammonia nitrogen was determined by the method of Niss (1957) as adapted to this culture system by Ecker and Lockhart (1961b). All dilutions were made with distilled water and optical densities were determined at 615 mn against a distilled water-reagent blank.…”
Section: Substratementioning
confidence: 99%
See 2 more Smart Citations